Increasing Native Research Leadership Through an Early Career Development Program - Ivanich, Jerreed D.; Sarche, Michelle; White, Evan J.; Marshall, Sarah Momilani; Russette, Helen; Ullrich, Jessica Saniguq; Whitesell, Nancy Rumbaugh (Frontiers in Public Health, 2022)
Inequities impact American Indian, Alaska Native, and Native Hawaiian populations across various health conditions; in particular, many Native communities bear a disproportionate burden of substance use disorder. Such inequities persist despite concerted efforts of communities and significant research directed toward prevention and intervention. One factor hampering these efforts is the underrepresentation of researchers who are themselves Native and uniquely equipped to respond to the needs of their communities. This paper describes the innovative Native Children's Research Exchange (NCRE) Scholars program, now entering its ninth year of successful career development support for emerging Native scholars. We summarize the history of NCRE Scholars, outline the mentoring and training approaches taken to meet the unique needs of early-career Native scholars, and present key progress of program alumni. The current cohort of Scholars provide first-person perspectives on how four key program elements have supported their career development to date. NCRE Scholars has been an effective approach for supporting the next generation of Native research leaders and for helping to build an essential mass of Native researchers prepared to respond to Native community health priority needs.